Semiotika dalam Album Manusia dan Monokrom Karya Tulus dan Implikasinya terhadap Pembelajaran Teks Puisi di Kelas X SMA - Eva Febriyanti; Erwan Kustriyono (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Language and semiotics have a close relationship and are interrelated. Language is a system of signs that humans use to communicate, while semiotics is the science that studies signs. Semiotics is a science that studies signs. This paper aims to describe the semiotic studies contained in the lyrics of the albums "Human" and "Monochrome". Apart from that, it also describes the albums "Humans" and Monochrome" as learning material for analyzing poetry texts in class X SMA. This research uses a descriptive approach using a qualitative method. The descriptive approach utilizes data in the form of a deep understanding of the use of semiotic signs in song lyrics, as well as being able to understand the meaning and context in their use. The conclusion of the analysis is as follows: Study of the semiotics of the lyrics of the albums "Manusia" and "Monochrome" by Tulus, that the signifiers found in this research are in the form of song lyrics, in the form of the suffixes a, u, i, ng, ar, am, ang. The signified found in this research is related to social reality, has meaning regarding the value of motivation towards other people, the value of optimism, and the value of love for someone as a whole of the song lyrics. The album "Human" and Monochrome" by Tulus can be used as learning material to analyze poetry texts in class X high school. Learning the semiotics of a collection of song lyrics from Tulus can improve students' ability to understand feelings, imagination, sensitivity and understanding of the characters depicted.